The crisis of school violence: a new perspective - King, Marianna (Michigan State University Press, 2021)
The causes of violence: standard explanations -- Standard practices -- Paolo Freire and the question of human nature -- The culture of violence -- The culture of school violence -- School shooters: more lethal than ever -- Media reality -- Fun and games -- Brain response to electronic media and games -- The future of violence -- What we can do: the opportunity.